Observation of interspecies ion separation in inertial-confinement-fusion implosions. (24th October 2016) - Hsu, S. C.; Joshi, T. R.; Hakel, P.; Vold, E. L.; Schmitt, M. J.; Hoffman, N. M.; Rauenzahn, R. M.; Kagan, G.; Tang, X.-Z.; Mancini, R. C.; Kim, Y.; Herrmann, H. W.
Abstract: We report direct experimental evidence of interspecies ion separation in direct-drive, inertial-confinement-fusion experiments on the OMEGA laser facility. These experiments, which used plastic capsules with D2 /Ar gas fill (1% Ar by atom), were designed specifically to reveal interspecies ion separation by exploiting the predicted, strong ion thermo-diffusion between ion species of large mass and charge difference. Via detailed analyses of imaging x-ray-spectroscopy data, we extract Ar-atom-fraction radial profiles at different times, and observe both enhancement and depletion compared to the initial 1%-Ar gas fill. The experimental results are interpreted with radiation-hydrodynamic simulations that include recently implemented, first-principles models of interspecies ion diffusion. The experimentally inferred Ar-atom-fraction profiles agree reasonably, but not exactly, with calculated profiles associated with the incoming and rebounding first shock.